Electrophoresis Technique for Varietal Identification and Genetic Purity in Hybrid Cotton (Gossypium hirsutum L.) - ARUNITA RAKSHIT; V. VASHISHT; S. RAKSHIT; M. DADLANI (Seed Research, 2026)
Genetic purity is an essential component of seed quality. To ensure the genetic purity of hybrid cotton seeds, seed certification agencies follow the grow out tests which are labour intensive, tedious and time consuming. In post-GATT scenario establishing varietal identity is crucial for protection of plant varieties. In this regard Distinctness, Uniformity and Stability (DUS) tests play an important role and also it has been recommended by the UPOV. Our objective was to identify biochemical markers to establish distinctness and uniformity of cotton hybrids and parental lines and possible application of these markers for genetic purity analysis.